EFEKTIFITAS PENERAPAN PROGRAM SISTEM INFORMASI MANAJEMEN PUSKESMAS PADA PUSKESMAS MATARAM TAHUN 2022 - Hilda Astuti; Sujarwoko Sujarwoko (Nusadaya Journal of Multidiciplinary Studies, 2022)
The Puskesmas Management Information System (SIMPUS) is an arrangement that provides information so that it can assist the decision-making process for carrying out Puskesmas management in achieving the goals and objectives of its activities. This study aims to identify the effectiveness of the implementation of the puskesmas management information system (simpus) at the Mataram Health Center in 2022. This research is a research using descriptive quantitative research methods. Sempel in this study were 100 respondents who were outpatients at the Mataram Health Center. The data collection tools and methods used were questionnaire sheets through the interview method which were conducted from April to June 2022. The data analysis used was univariate analysis to explain or describe the research variables. The results of univariate analysis on the variable effectiveness of the implementation of the puskesmas management information system program at the Mataram Puskesmas showed that patient perceptions of the Effectiveness of the Implementation of the Puskesmas Management Information System which were considered less effective amounted to 12 people with a percentage of 12.0% and patient perceptions that were effective amounted to 54 people with a percentage of 54 .0%. And finally, the perception of patients who were considered very effective was 34 people with a percentage of 34.0%. Based on the table, it can be seen that the percentage of patients who feel effective is higher, namely as many as 54 people with a percentage of 54.0%. It is hoped that the puskesmas can increase the effectiveness of implementing the puskesmas management information system in order to increase patient satisfaction. The puskesmas is also expected to conduct regular effectiveness surveys in an effort to improve the quality of health services.